Effect of temperature and light on the quality of extra virgin olive oil produced in Rio Grande do Sul (Research, Society and Development, 2022)
The objective of the study is to evaluate the quality standards of olive oils produced in the Campanha region of Rio Grande do Sul, compared to storage under different conditions of light and temperature. The experimental design was completely randomized in a three-factor scheme: incidence of temperature (25 and 30°C), incidence of luminosity (0 and 300 Lux) and storage time (0, 1, 2 and 3 months), evaluating the peroxide content; free acidity; specific quenching in the ultraviolet; total chlorophylls, antioxidant activity; total carotenoids; total phenols and sensory evaluation. It was obtained, free acidity of 0.49 g oleic acid.100 g-1, peroxide index of 7.90 mEq O2.kg-1, K232 equal to 2.48, K270 equal to 0.15, total phenols of 273.02 mg GAE.kg-1, total chlorophylls of 37.72 mg phaeophytin α.kg-1, antioxidant activity of 24.39%, total carotenoids of 11.81 mg β-carotene.kg-1, aroma with average overall equal to 6.75, flavor with 6.58 and purchase intent of 3.75. The luminosity influenced increasing the values ​​of free acidity, specific extinction, decreasing the values ​​of total phenols, total carotenoids and total chlorophylls. The temperature influenced increasing the values ​​of free acidity, K232 and also decreasing the values ​​of total carotenoids and total chlorophylls. Time significantly influenced all analyses, except for total phenols, causing the same decrease and increase effects as light and temperature on the analyses. It follows that the quality of olive oil is affected by the conjuncture of storage factors adopted.